2014
DOI: 10.1111/ijd.12399
|View full text |Cite
|
Sign up to set email alerts
|

Skin photoprotection and consumption of coffee and polyphenols in healthy middle‐aged Japanese females

Abstract: Coffee and polyphenol consumption was associated with low facial pigmented spots in Japanese middle-aged females. We speculated that coffee helps protect human skin from photoaging, and polyphenols, including chlorogenic acids, may contribute to the decreased hyperpigmentation of pigmented spots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…showed the pigmented spots increased by age and subjects living in southern area shows more hyperpigmented . VISIA ™ is a facial image analyzer, and we also observed a correlation of VISIA pigment spot scores and age in middle‐aged Japanese women with low coffee consumption. However, there has been no information of UV pigment spot status in younger generation and also onset age when pigmented spots appear.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…showed the pigmented spots increased by age and subjects living in southern area shows more hyperpigmented . VISIA ™ is a facial image analyzer, and we also observed a correlation of VISIA pigment spot scores and age in middle‐aged Japanese women with low coffee consumption. However, there has been no information of UV pigment spot status in younger generation and also onset age when pigmented spots appear.…”
Section: Introductionmentioning
confidence: 62%
“…Skin condition measurements were conducted as described at the previous report . Briefly, pigmented spot scores were measured by the facial image analysis system VISIA ™ Evolution (Canfield Inc., Fairfield, NJ, USA) using ultraviolet light (UV pigmented spots) (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with an initially low RR included 7 individuals in the CPP group and 8 individuals in the Placebo group (a total of 15 subjects). The results of RR analysis of those two subgroups revealed that the RR-increasing effects of CPPs were more pronounced than in the comparison of the final analysis set, and the difference between these two subgroups was significant (F (1,14)511.6, p,0.01) at 4 wk (Fig. 4B).…”
Section: ) Scaly Skin In the Low Rr Groupmentioning
confidence: 92%
“…The subjects of this study included healthy Japanese women between 25 and 35 y of age. This study was approved by the Ethics Committee of the Kao Corporation in accordance with the principles of the Declaration of Helsinki (Approval number: [13][14][15][16][17][18][19][20][21][22][23][24]. In addition, subjects only participated after receiving a sufficient explanation of the purpose and content of the study and providing informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation